Effects of colchicine adjuvant therapy on disease control, serum NALP3, sICAM-1, MMP-9 and MMP-13 in patients with coronary heart disease and acute gout attack: Colchicine Effects on Coronary Disease and Acute Gout Markers - Wang, Bingxun; Liu, Yongqing; Han, Wenya; Li, Bing; Pang, Jie; Yang, Wenwen; Ma, Zengcai; Xu, Zesheng (Journal of Medical Biochemistry, 2024)
Background: To investigate the impact of colchicine adjuvant therapy on disease control and serum levels of nucleotide-binding oligomerization domain-like receptor (NALP) 3, soluble intercellular adhesion molecule (sICAM)-1, matrix metalloproteinase (MMP)-9, and MMP-13 in patients with coronary heart disease (CHD) complicated by acute gout attacks.Methods: Ninety-two patients with CHD and acute gout attacks admitted to our hospital from October 2021 to January 2023 were randomly divided into an observation group and a control group, with 46 patients in each group. The control group received conventional treatment, while the observation group received colchicine adjuvant therapy on top of the control group's treatment for 7 days. Clinical efficacy in both groups was assessed. Before and after treatment, cardiac function indicators (left ventricular ejection fraction (LVEF), left ventricular end-diastolic diameter (LVEDD), left ventricular posterior wall thickness (LVPWT)), vascular endothelial function indicators (sICAM-1, endothelin-1 (ET-1), and vascular endothelial growth factor (VEGF)), inflammatory factors (NALP3, MMP-9, MMP-13) levels, changes in immune cell populations (CD3+ lymphocytes, CD3+CD4+ lymphocytes, CD3+CD8+ lymphocytes ratio, and CD3+CD4+/CD3+CD8+ ratio) were compared, and the incidence of adverse reactions was recorded. Three months after treatment, the occurrence of major adverse cardiovascular events was also recorded.Results: The total effective rate in the observation group was significantly higher than that in the control group (93.48% vs 79.07%) (P
Keywords: Colchicine; Coronary heart disease; Acute gout attack; Nucleotide binding oligomerization domain-like receptor protein 3; Soluble intercellular adhesion molecule-1; Matrix metalloproteinase-9; Matrix metalloproteinase-13; Cardiac function